2009
DOI: 10.1152/ajpcell.00478.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on l- and d-methionine uptake across the apical membrane of Caco-2 cells

Abstract: The transport systems involved in intestinal methionine (Met) absorption are described as Na ϩ -dependent and Na ϩ -independent mechanisms. However, since recent studies have suggested the importance of the H ϩ gradient as a driving force for intestinal nutrient absorption, the aim of the present work was to test whether Met transport across the apical membrane of Caco-2 cells is affected by extracellular pH. The results show that Land D-Met uptake was increased by lowering extracellular pH from 7.4 to 5.5, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Previous data on plasma methionine are scarce and one paper (Tessari et al 2005) shows that it is not changed in diabetic patients, while we found a significant increase in methionine. However, considering that taurine inhibits methionine uptake in some cell models such as intestinal Caco-2 cells (Martin-Venegas et al 2009) the observed increase in methionine could be biologically plausible.…”
Section: Discussionmentioning
confidence: 97%
“…Previous data on plasma methionine are scarce and one paper (Tessari et al 2005) shows that it is not changed in diabetic patients, while we found a significant increase in methionine. However, considering that taurine inhibits methionine uptake in some cell models such as intestinal Caco-2 cells (Martin-Venegas et al 2009) the observed increase in methionine could be biologically plausible.…”
Section: Discussionmentioning
confidence: 97%
“…Absorption of an amino acid depends on concentration, character and side chain as well as on the presence of other amino acids (Chakrabarti, ; Frenhani & Burini, ; Bröer, ; El‐Kattan & Varma, ). Assuming as a reference the normal concentration in the intestinal lumen, amino acids with short side chain, such as glycine and taurine, are slowly transported when in lower concentration and vice versa ; amino acids with lipophilic side chain, such as methionine, phenylalanine and tryptophan, are rapidly transported when in lower concentration and vice versa ; acidic amino acids, such as aspartic acid and glutamic acid, are rapidly transported when in higher concentration and vice versa ; dibasic amino acids, such lysine and arginine, are always slowly transported (Martín‐Venega et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, intracellular l ‐Met inhibits l ‐arginine efflux and this results in a stimulation of net l ‐arginine uptake , confirming a previous study demonstrating that l ‐Met and l ‐citrulline stimulate l ‐arginine uptake . Taurine supplementation has also been suggested to reduce Met absorption , and this was used to explain the reduced Met and homocysteine levels in the blood of rabbits fed an atherogenic diet supplemented with taurine .…”
Section: Efficiency and Complexity Of Gastrointestinal Methionine Absmentioning
confidence: 99%